ANALYSIS OF MATURITY LEVELS OF ICT UTILIZATION ON EAST JAVA’S MICRO, SMALL, MEDIUM ENTERPRISES (MSMEs) IN THE NEW HABITS ADAPTATION ERA - Amalia, Siska; Affandi, Achmad; Sumpeno, Surya (JAREE (Journal on Advanced Research in Electrical Engineering), 2022)
The use of information and communication technology has increased along with the Covid-19 pandemic in early 2020 which made the whole world turn into digitalization. This study focuses on analyzing the maturity level of ICT utilization on East Java’s MSMEs using the Business Model Canvas (BMC) approach and the Capability Maturity Model ISAC FOUNDATION (2007) and evaluating gaps. The results of the analysis shows the maturity average of ICT utilization in East Java’s MSMEs is 0.86, which is at Level 1 (Initial), the gap average is 2,13 and the gap maturity value in ICT utilization in East Java’s MSMEs is Large, that is 1,5.Keywords—ICT, Maturity Level, MSMEs